Ethical and deontological principles n Physiotherapy. Your Comparison with other health professions - Gomez Conesa, A; Carles Hernandez, R; Perez-Carceles, M A D; Osuna Carrillo de Albomoz, E (Cuestiones de Fisioterapia, 1999)
Deontology is the set of norms of professional conduct to be respected by the practitioner. When these norms are established in the code of Professional Practice they have the weight of rules for the professionals to whom they are directed and failure to comply can be sanctioned. In this study we review the procedural norms of physiotherapist and go to compare them with those of other health professionals. The results demonstrate close correspondence between the codes of practice governing these professions.